2013
DOI: 10.2753/pss0885-3134330109
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping, Affiliation, and Self-Stereotyping of Underrepresented Groups in the Sales Force

Abstract: This study adds theoretical and managerial insights to the sales literature regarding the unfortunate but prevalent issue of stereotyping in sales by supervisors toward underrepresented groups of sales employees. Specifically, we examine (1) the self-evaluative, social, and emotional consequences of being stereotyped by a supervisor, and (2) the moderating role of employees' self-construal (i.e., the employee's level of independence versus interdependence) as it relates to their responses toward a supervisor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…According to self-categorization theory (Hogg & Turner, 1987;Turner, 1987), selfcategorization leads to self-stereotyping, wherein an individual "systematically biases selfperception and behaviour to render it more closely in accordance with stereotypic ingroup characteristics and norms" (Hogg & Turner, 1987, p. 326). Research has indicated that the more salient a self-categorization, the more individuals are likely to self-stereotype, by describing themselves by the characteristics of the group prototype (e.g., Hogg & Turner, 1987;Pickett et al, 2002;Simon & Hamilton, 1994;Spears et al, 1997;Yang, Hansen, Chartrand, & Fitzsimons, 2013). Self-stereotyping has been assumed to occur by indexing the degree to which group members not only define themselves by the characteristics of the ingroup but also reject the characteristics of the outgroup (e.g., Brown & Turner, 1981;Cadinu et al, 2013;Simon & Hamilton, 1994;Turner, 1982).…”
Section: Self-stereotypingmentioning
confidence: 99%
“…According to self-categorization theory (Hogg & Turner, 1987;Turner, 1987), selfcategorization leads to self-stereotyping, wherein an individual "systematically biases selfperception and behaviour to render it more closely in accordance with stereotypic ingroup characteristics and norms" (Hogg & Turner, 1987, p. 326). Research has indicated that the more salient a self-categorization, the more individuals are likely to self-stereotype, by describing themselves by the characteristics of the group prototype (e.g., Hogg & Turner, 1987;Pickett et al, 2002;Simon & Hamilton, 1994;Spears et al, 1997;Yang, Hansen, Chartrand, & Fitzsimons, 2013). Self-stereotyping has been assumed to occur by indexing the degree to which group members not only define themselves by the characteristics of the ingroup but also reject the characteristics of the outgroup (e.g., Brown & Turner, 1981;Cadinu et al, 2013;Simon & Hamilton, 1994;Turner, 1982).…”
Section: Self-stereotypingmentioning
confidence: 99%
“…anger, hurt, sadness, embarrassment and frustration. Other previous (2) Drives people apart ( 1) Humble (2) Ignore (3) Laugh (9) Motivated to improve ( 8) Performance affected (5) Prove stereotype to be correct (9) Prove stereotype wrong (14) Taken advantage o f(l) Working hard (3) Emotional (47) Angry (6) Bad (2) Demoralised; worthless (3) Demotivated (4) Disappointed (1) Embarrassed (3) Frustrated (5) Hate (1) Hurtful (6) Irritated (2) Isolated (7) Sad (3) Unappreciated (1) Uncomfortable ( (Block et a l, 2011;Pious, 2003;Yang, Hansen, Chartrand, & Fitzsimons, 2013). According to Glomb and Hulin (1997), when in dividuals are under stereotype threat, they are unable to openly express their anger because it is viewed as socially unacceptable within the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…São profissionais que levam em conta não só os seus próprios interesses, mas também os de outros, por isso, tendem a ganhar a confiança de outras pessoas com maior facilidade e a construir melhores relações sociais com os colegas de trabalho, clientes e com o próprio chefe (Erevelles & Fukawa, 2013;Stan, Evans, Arnold, & Mcamis, 2012;Yang, et al, 2013).Os vendedores processam, interiorizam e gerenciam cargas cada vez maiores de informações e precisam ser pessoas capazes de atender a clientes de diferentes crenças e necessidades (Amyx & Bhuian, 2009;Spiro&Weitz, 1990).…”
Section: O Trabalho Em Vendasunclassified
“…Cientes da crescente importância da força de vendas em uma organização, gerentes estão mais preocupados em manter os vendedores motivados e satisfeitos com o trabalho. Neste contexto, saber sobre a satisfação no trabalho dos profissionais de vendas é algo relevante e um tanto desafiador, ainda mais que os funcionários da área de vendas exercem uma função de "limite" na interface entre a organização e o seu ambiente de mercado (Amyx & Bhuian, 2009;Churchill, Ford, & Walker, 1974;Lagace, Goolsby & Gassenheimer, 1993;Yang, Hansen, Chartrand, & Fitzsimons, 2013).…”
unclassified